A Delegation of Christians from Najran Visits the Prophet Muhammad: Contemporary English Sirah Literature for a Western Audience - Mirza, Mahan H. (Islamic Studies, 2011)
This paper classifies three recent Sirah works in English according to the typology in Tarif Khalidi’s Images of Muhammad. By looking at the treatment of the Najran story in the Sirah works of Tariq Ramadan, Martin Lings, and M. A. Salahi, the paper concludes that they are shaped by the approaches of the “late medieval” to “contemporary” authors of Sirah. This makes the works either encyclopedic or highly selective, with the material arranged in order to appeal to a specific audience. Such a treatment of the sources is neither satisfactory nor credible for a scholarly or critical audience. Muslim scholars of today may need to take a cue from Western methods by wedding theological reflection with historical criticism. The paper suggests that it is possible to draw positive theological messages from classical Sirah narratives that appear, at first glance, to be problematic.